A Cyber-Physical Approach to Black Soldier Fly Cultivation: Integrating IoT Monitoring with Adaptive Watering Control - Rini Puji Astutik; Arbi Alfian Mas'ud; Muhammad Ramadhani; Samsudin Nur; Soffa Zahara; Mohammad Muslimin (PT. Global Research Collaboration, 2026)
This article details the creation and deployment of an IoT-integrated system designed for the activated watering and environmental supervision of Black Soldier Fly (BSF) maggot production. Given that maggot yield is heavily reliant on precise climate control, traditional manual techniques often fall short due to their labor-intensive nature and susceptibility to human error. The implemented solution utilizes an ESP32 microcontroller interfaced with an SHT20 sensor to monitor temperature and humidity, managing three key actuators: a heating element, a cooling fan, and a water pump. Communication is facilitated through the Telegram Bot API, offering both a manual override and an autonomous mode driven by a Mamdani fuzzy logic engine. Experimental results confirmed the system's high precision, with temperature and humidity sensing showing accuracies of 99.13% and 99.27%, respectively. Furthermore, evaluations of the fuzzy logic controller across 12 trials proved its capability to maintain optimal conditions without operational conflicts. This system offers a scalable approach to modernizing insect-based agriculture by stabilizing environmental parameters and reducing operational overhead